2005
DOI: 10.5194/aab-48-305-2005
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the development of the claws in new born calves of different breeds and crossbreds using Dual Energy X-Ray Absorptiometry (DXA)

Abstract: This study evaluated claw development in 199 calves of different genetic background during the first 70 days of life. Dual Energy X-Ray Absorptiometry (DXA) was found to be a useful tool for this purpose. By the means of DXA, in humans as in animals, body constitution and composition can be examined in vivo. Thus, the whole body or body regions can be analyzed for the content of fat tissue, lean tissue, bone mineral content and bone mineral density. Large differences in claw parameters were observed, depending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(4 reference statements)
0
2
0
1
Order By: Relevance
“…Considering that deposition of the bone matrix is a characteristic of vertebrate growth, it was postulated that a higher bone density value of certain skull features should be observed in older skulls. Deposition of bone matrix is indeed a dynamic process that continues through the life span of mammals as attested by various studies on bone growth and mineralization processes inferred through the bone mineral density (BMD) measurements of various domestic mammal species (Martin et al,1981; Munday et al,1994; Lauten et al,2000,2001,2002; Mitchell et al,2001; Nüske et al,2002; Zotti et al,2004; Ekici et al,2005). These studies have shown that body weight is the most important intra and interspecific factor directly affecting bone mineral content and density.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that deposition of the bone matrix is a characteristic of vertebrate growth, it was postulated that a higher bone density value of certain skull features should be observed in older skulls. Deposition of bone matrix is indeed a dynamic process that continues through the life span of mammals as attested by various studies on bone growth and mineralization processes inferred through the bone mineral density (BMD) measurements of various domestic mammal species (Martin et al,1981; Munday et al,1994; Lauten et al,2000,2001,2002; Mitchell et al,2001; Nüske et al,2002; Zotti et al,2004; Ekici et al,2005). These studies have shown that body weight is the most important intra and interspecific factor directly affecting bone mineral content and density.…”
Section: Introductionmentioning
confidence: 99%
“…Although the rat is the most frequently used mammal in DXA-based investigations, the BMD of several species of larger-sized nonhuman mammals has already been reported [1]. Studies on a single specific bone or total body BMD have been performed on nonhuman primates [2,3], sheep [4], bovine calves [5,6], horses [7], pigs [8], dogs [9,10], cats [11], and striped [12] and bottlenose dolphins [13]. All BMD values (expressed as g/cm 2 ) obtained from the species listed above ranged between 0.463 (canine III metacarpal bone) and 2.12 (pig skull).…”
mentioning
confidence: 99%
“…Intention dieser Arbeit ist es, im Rahmen eines Kreuzungsversuches zwischen den Rassen Deutsches Fleckvieh und Deutsche Holsteins das DXA Verfahren erstmals bei Kälbern in vivo einzusetzen, um damit Erkenntnisse über deren Wachstum und Kör-perzusammensetzung zu erlangen. Diese Studie ist Teil eines Projektes, das sich außerdem mit der Untersuchung des Klauenwachstums bei neugeborenen Kälbern befasst (NÜSKE et al, 2002) sowie in einer noch andauernden Studie Referenzuntersuchungen zwischen DXA-Analyse und Totalzerlegung (MUSICK, persönliche Mitteilung) befasst. Die DXA-Untersuchung zählt zu den häufig in der Humanmedizin angewendeten Techniken zur Ermittlung der Körperzusammensetzung und zeigt eine sehr große Prä-zision und Genauigkeit.…”
unclassified